Beggar-Homeless and Street Children in Cultural-Social Perspective - Ani Mardiyati (Balai Besar Penelitian dan Pengembangan Pelayanan Kesejahteraan Sosial, Kementerian Sosial, 2015)
This study is meant to unravel the problem in social and cultural perspective on the handling held by government and non-government for beggar-homeless at the institution and street children at the transit house. The prevalency of beggar and street children indicates the government needs to overcome that problem socially and culturally. From social perspective, beggar-homeless and street children are part of society where they embeded socially structurelye. The existence of beggar-homeless and street children in the city associated as a problem that is identic with dirtyness, even thieve and stoling. As part of governmental social structure, beggars and street children should be seen as an object of handling so that they are not a threat to general order but they can be a community supporting city development, perticularly. Cultural handling that treat beggar-homeless and street children as civilized community. Educate positive mental and spirit that currently they put aside is one effort to bring back to normative conduct as member of civilized community. Besides that, it needs capitalizing skill education for beggar-homeless and street children when they work and create later. The last effort that can be done is to bring them to the place of origin, with governmental coordination handling and to provide work chance at the place of origin, with coordinated handling to provide work chance at the place of origen they left before, for example with utilizing many-workers-job program. With this effort rural people are expected to live comfortably in the village. The float of urbanization will not get bigger and bring a problem in the urban area. In future, it needs rural human recources planning, especially in infertile and dry areas with its people living normally.